2019
DOI: 10.12991/jrp.2019.159
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical study and biological activities of Scurrula parasitica L (Loranthaceae) leaves

Abstract: Chemical constituents of Scurrula parasitica leaves from Loranthaceae family and some biological activities have been studied. Cold extractions were carried out using n-hexane, ethyl acetate and methanol to obtain the crude extracts. Purification of the extracts led to the isolation of quercetin 1, quercitrin 2, kaempferol 3-O--L-rhamnoside 3, (+)-catechin 4, lupeol 5, lupeol palmitate 6, -sitosterol 7, squalene 8, octacosane 9, octadecane 10 and eicosane 11. The in vitro antioxidant activity of the extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In southern Ecuador, is has been located in different sites, such as Cajanuma and Saraguro, among others [10]. The Loranthaceae family has been reported to have anti-inflammatory [11], antioxidant [12,13], antimalarial [14], antimicrobial, antiviral [15], and gastrointestinal properties [16]. Some studies performed in this family have reported the presence of glycosylated flavonoids [17] and cardiac glucosides [18].…”
Section: Introductionmentioning
confidence: 99%
“…In southern Ecuador, is has been located in different sites, such as Cajanuma and Saraguro, among others [10]. The Loranthaceae family has been reported to have anti-inflammatory [11], antioxidant [12,13], antimalarial [14], antimicrobial, antiviral [15], and gastrointestinal properties [16]. Some studies performed in this family have reported the presence of glycosylated flavonoids [17] and cardiac glucosides [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tiegh., a semiparasitic plant grown in Saudi Arabia, traditionally used as a cure for diabetes and cancer in human, a flavonoid quercetin, (-)-catechin, and a flavane gallate 2S,3R-3,3´,4´,5,7pentahydroxyflavane-5-O-gallate, were isolated from the aerial parts (Orfali et al, 2019). Cold extractions of S. parasitica leaves were carried out using n-hexane, ethyl acetate and metanol to obtain the crude extracts, and purification of the extracts led to isolation of quercetin, quercitrin, kaempferol 3-O-α-L-rhamnoside, (+)-catechin, lupeol 5, lupeol palmitate, ꞵ-sitosterol, squalene, octacosane, octadecane and eicosane (Muhammad et al, 2019). Only polyphenols and four flavonoids, two glycosidated (kaempherol glicoside and quercetin glicoside) and two non-glycosidated (kaempherol and quercetin), were detected in the study carried out on P. linearis, without deepening in the isolation and identification of other secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…and Pseudomonas sp., all of which are known to be associated with either crown gall or gastrointestinal tract and wound infections (Deeni & Sadiq, 2002). Likewise, all extracts and isolated compounds of S. parasitica leaves showed weak activity on antimicrobial activity against two Gram-positive bacteria (Staphylococcus aureus and Bacillus subtilis), two Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) and a fungi (Aspergillus niger) with the exception of quercetin which exhibited moderate activity against P. aeruginosa with MIC and MBC value of 250 μg/mL (Muhammad et al, 2019). In the study with P. linearis, although the results were only significant with strains of Staphylococcus aureus, its is necessary to carry out other tests with different strains of bacterial species of wide prevalence in hospital infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These Petri dishes were kept as it is for one-hour diffusion at room temperature and then for incubation at 37 0 C for 24 hours in an incubator. The extent diameter of inhibition after 24 hours was measured as the zone of inhibition in millimeters [16][17][18][19].…”
Section: Antibacterial Activitymentioning
confidence: 99%